Local versus non-local effects of Chinese media and post-earnings announcement drift - Kim, Jeong-Bon; Li, Liuchuang; Yu, Zhongbo; Zhang, Hao (Journal of Banking & Finance, 2019)
Taking advantage of the institutional difference in capture between local and non-local media in China, we examined the association between media capture and post-earnings announcement drift (PEAD). Using both portfolio and regression analyses, we found that, for the same firms, non-local media coverage is negatively associated with PEAD; however, there is no association between local media coverage and PEAD, except for non-state-owned firms. Given that in China, non-local media are less captured or more independent than local media, the negative association observed for non-local media coverage can be interpreted as an indication that media independence plays a role in reducing PEAD or improving informational efficiency in the stock market.